Influence of toothbrushing, eating and smoking on Dentocult SM Strip mutans test scores - Schlagenhauf, U; Pommerencke, K; Weiger, R (Oral microbiology and immunology, 1995)
The Dentocult SM Strip mutans test (D-SM, Vivadent) is a popular method for estimating salivary mutans streptococci and is clinically used for the detection of potential caries risk patients. The influence of toothbrushing, eating and smoking on the reliability of D-SM test scores was assessed in 30 subjects aged 21-39 years. All experiments were performed 24 h after professional tooth cleaning in the morning of 3 consecutive days. On day 1 immediately before and 30 min after toothbrushing, D-SM tests were taken and total salivary colony-forming units per ml were determined. Following the same protocol, the influence of a standardized breakfast and of smoking was evaluated on day 2 and on day 3 respectively. Although all parameters significantly decreased the salivary colony-forming units per ml, only the standardized breakfast induced significant changes in the D-SM test results. Eating therefore should be avoided prior to the performance of the D-SM test.